Anemia and Idiopathic Intracranial Hypertension: A Systematic Review and Meta-analysis. Issue 1 (March 2022) - Yu, Caberry W.; Waisberg, Ethan; Kwok, Jason M.; Micieli, Jonathan A.
Abstract : Background: Idiopathic intracranial hypertension (IIH) is a condition typically affecting young, obese women. Although anemia is recognized as a risk factor of IIH from case reports, their relationship remains controversial as several comparative studies showed no significant association. This study aimed to examine the relationship between anemia and IIH. Methods: MEDLINE, Embase, Cochrane Library, and grey literature were searched to September 2020. Primary studies on patients with diagnoses of anemia of any kind and IIH were included. Primary outcomes included the total number of cases of anemia and IIH. A meta-analysis on the prevalence of anemia in IIH compared with control patients was conducted. Grading of Recommendations, Assessment, Development and Evaluations (GRADE) was used to rate the quality of evidence. Results: Overall, 62 cases and 5 observational or case–control studies were included. Pooled incidence of anemia in patients with IIH was 195/1, 073 (18.2%). Patients with IIH (n = 774) had a significantly higher prevalence of anemia compared with controls (n = 230, 981) (RR 1.44 [95% confidence interval 1.08–1.92]). Patients were 67.7% females and had a mean age of 22.4 years. The mean opening pressure was 37.9 cmH2O. Anemia was most commonly caused by iron deficiency (51.6%) and aplastic anemia (19.4%). Most patients (59.7%) showed improvement or resolution with anemia treatment only without intracranial pressure-lowering therapy. Evidence was limited because of high risk of reporting bias from the large number of case reports and case–control studies. Conclusions: Anemia is significantly more common in IIH compared with control patients, and case reports suggest a direct relationship. Complete blood counts should be considered in all patients with papilledema, particularly in atypical presentations (male, nonobese, nonperipapillary retinal hemorrhages, prominent risk factor for anemia) or in treatment-refractory IIH.